A Comparative Study of the Inclusion Complexes of 2-[5'-benzylidene-2'-phenyl-4'-oxo-1', 3'-thiazolidine]-1, 3-benzothiazole and 2-[5'-(p-N,N-dimethylamino- benzylidene)-2'-phenyl-4'-oxo-1', 3'-thiazolidine]-1, 3-benzothiazole withβ-Cyclodextrin - S. Panda; S. K. Dash (E-Journal of Chemistry)
The compounds 2-[5'-benzylidene-2'-phenyl-4'-oxo-1', 3'-thiazolidine]-1, 3-benzothiazole and 2-[5'-(p-N,N-dimethylamino- benzylidene)-2'-phenyl-4'-oxo-1', 3'-thiazolidine]-1, 3-benzothiazole have been synthesized in their purest forms starting from 2-aminobenzothiazole. The inclusion complexes of the above compounds have been prepared with β-cyclodextrin to increase their solubility and bioaccessibility in polar medium. The formation of inclusion complexes have been ascertained by study of spectral characteristic before and after inclusion complex formation. The stability of inclusion complexes and nature of interaction between the host and guest are known from the determination of thermodynamic parameters. Further the antibacterial and antifungal activities of the compounds are determined which is found to increase significantly after inclusion complex formation